Bidirectional reporter assay using HAL promoter and TOPFLASH improves specificity in high‐throughput screening of Wnt inhibitors. Issue 12 (29th August 2017) - Yamaguchi, Kiyoshi; Zhu, Chi; Ohsugi, Tomoyuki; Yamaguchi, Yuko; Ikenoue, Tsuneo; Furukawa, Yoichi
Abstract: Constitutive activation of Wnt signaling plays an important role in colorectal and liver tumorigenesis. Cell‐based assays using synthetic TCF/LEF (T‐cell factor/lymphoid enhancer factor) reporters, as readouts of β‐catenin/TCF‐dependent transcriptional activity, have contributed greatly to the discovery of small molecules that modulate Wnt signaling. In the present study, we report a novel screening method, called a bidirectional dual reporter assay. Integrated transcriptome analysis identified a histidine ammonia‐lyase gene ( HAL ) that was negatively regulated by β‐catenin/TCF‐dependent transcriptional activity. We leveraged a promoter region of the HAL gene as another transcriptional readout of Wnt signaling. Cells stably expressing both an optimized HAL reporter and the TCF/LEF reporter enabled bidirectional reporter activities in response to Wnt signaling. Increased HAL reporter activity and decreased TCF/LEF reporter activity were observed simultaneously in the cells when β‐catenin/TCF7L2 was inhibited. Notably, this method could decrease the number of false positives observed when screening an inhibitor library compared with the conventional TCF/LEF assay. We found that Brefeldin A, a disruptor of the Golgi apparatus, inhibited the Wnt/β‐catenin signaling pathway. The utility of our system could be expanded to examine other disease‐associated pathways beyond the Wnt/β‐catenin signaling pathway. Abstract : The establishment of a well‐designed high throughput screening system is a key step to identify small molecules that inhibit a signaling pathway or a molecule of interest. The authors established cells expressing both a histidine ammonia‐lyase ( HAL ) promoter reporter and the TCF/LEF reporter that enabled bidirectional reporter activities in response to Wnt signaling. This assay system efficiently removed false positives in the screening of chemical libraries, and this approach could be applied to discover chemicals that target other signaling pathways.